Carbon Fiber Strengthening of Geopolymer Concrete Wall Panels with Iron Fillings - Wissam K. Al-Saraj, Dr.; Layth Abdulbari Al-Jaberi, Dr.; J. AL-Serai, Sahar; ., . (International Journal of Engineering and Technology, 2018)
Wall is a vertical plate member resisting vertical (in-plane) or lateral loads. Load-Bearing walls were referred to RC wall panels which were commonly used as load-bearing structural members, braced and laterally supported by the rest of the structure, local materials such as Metakaolin and alkaline solutions are used to cast (600x400) mm reinforced concrete wall panels with 40 mm thickness. To find the ultimate bearing capacity and lateral deflection of wall panels. Seven specimens are dividedÂ in two groups to study the variation effect of iron filling (0, 0.5, 0.75 andÂ 1.0)%Â Â and carbon fiber (225, 125 and 90 )mm spacing center to center of strips.Â The result shows that the maximum increasing are 17% and 14% for ultimate bearing capacity and cracking load of wall panels respectively, when iron filling is 1%. Also, the using of carbon fiber with 90 mm spacing center to center of strips leds to increasing in ultimate bearing capacity and cracking load by 31% and 7% respectively. Lateral deflection of wall panels was measured and compared with the reference wall to investigate the strengthening effect.Â